1991
DOI: 10.2134/agronj1991.00021962008300030014x
|View full text |Cite
|
Sign up to set email alerts
|

Root Response of Tolerant and Intolerant Soybean Cultivars to Soybean Cyst Nematode

Abstract: Tolerance to soybean cyst nematode (SCN), Heterodera glycines Ichinohe, has been identified in soybean [Glycine max (L.) Merr.] and has potential as a management strategy to limit SCN yield suppression. Little information is available on the growth and morphology of roots of tolerant soybean cultivars parasitized by SCN. This study was conducted to compare root and vegetative responses of a moderately tolerant soybean, ‘Wright’, with an intolerant soybean, ‘Bragg’, to parasitism by SCN. In 1986, Bragg and Wrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 8 publications
1
22
1
Order By: Relevance
“…In our study, root tip production on plants inoculated with SCN alone was not different from that observed on non-inoculated controls. This trend was observed on both cultivars, and contrasts with research by Miltner et al (1991) showing an increase in root tip production on an SCN-tolerant cultivar. This discrepancy may be due to differences in cultivars, sources of resistance to SCN, or different SCN HG types tested in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our study, root tip production on plants inoculated with SCN alone was not different from that observed on non-inoculated controls. This trend was observed on both cultivars, and contrasts with research by Miltner et al (1991) showing an increase in root tip production on an SCN-tolerant cultivar. This discrepancy may be due to differences in cultivars, sources of resistance to SCN, or different SCN HG types tested in the two studies.…”
Section: Discussioncontrasting
confidence: 99%
“…One of the previously reported effects of SCN infection is increased branching of soybean roots, which has been observed in SCN tolerant cultivars (Radcliffe et al, 1990;Miltner et al, 1991). In our study, root tip production on plants inoculated with SCN alone was not different from that observed on non-inoculated controls.…”
Section: Discussionsupporting
confidence: 46%
“…The proportionately smaller root system of cv, Wright (Table 3) can be considered to be more efficient than that of cv, Bragg (Radcliffe et al, 1990;Miltner et al, 1991), Differences in root efficiency and nutrient absorption have been investigated in a number of species, including soyabean (Foote & Howell, 1964;Barber, 1982), In the greenhouse, overall SRR was greater in plants infested by SCN, The root systems may have increased their activity in order to compensate for the nematode-induced reduction in their size, as has been demonstrated elsewhere (Price et al, 1982), Differences between greenhouse and growth-chamber experiments also provide evidence of differences in the physiological characteristics of the root systems of the two varieties. In the greenhouse, cv, Wright responded to P with a much increased SRR, indicating a more efficiently functioning root system under conditions of higher fertility, whilst the SRR of cv, Bragg remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Miltner et al, (1991) reported that cyst nematodes suppressed soybean root growth on susceptible cultivars, whereas root growth of tolerant cultivars was stimulated by the presence of soybean cyst nematodes. The use of tolerant or nutrient-use-efficient cultivars may be an important practice to improve root growth in stress environments.…”
Section: Integrated Cropping Systems and Pest Managementmentioning
confidence: 99%